2009
DOI: 10.1093/hmg/ddp370
|View full text |Cite
|
Sign up to set email alerts
|

A conserved role for the mitochondrial citrate transporter Sea/SLC25A1 in the maintenance of chromosome integrity

Abstract: Histone acetylation plays essential roles in cell cycle progression, DNA repair, gene expression and silencing. Although the knowledge regarding the roles of acetylation of histone lysine residues is rapidly growing, very little is known about the biochemical pathways providing the nucleus with metabolites necessary for physiological chromatin acetylation. Here, we show that mutations in the scheggia (sea)-encoded Sea protein, the Drosophila ortholog of the human mitochondrial citrate carrier Solute carrier 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 38 publications
2
55
0
1
Order By: Relevance
“…Two approaches have been used to identify these new functions. The first is based on the inhibition of mitochondrial CIC activity by the specific substrate analogue 1,2,3-benzene-tricarboxylate (BTA) Infantino et al, 2011a;Cappello et al, 2012;Catalina-Rodriguez et al, 2012) and the second by siRNA gene silencing Morciano et al, 2009;Infantino et al, 2011a;Catalina-Rodriguez et al, 2012). Recently, by mutational analysis of the SLC25A1 gene (Edvardson et al, 2013;Nota et al, 2013), different mutations were identified in patients with agenesis of corpus callosum and hydroxyglutaric aciduria.…”
Section: The Multifunctional Role Of Citratementioning
confidence: 99%
See 3 more Smart Citations
“…Two approaches have been used to identify these new functions. The first is based on the inhibition of mitochondrial CIC activity by the specific substrate analogue 1,2,3-benzene-tricarboxylate (BTA) Infantino et al, 2011a;Cappello et al, 2012;Catalina-Rodriguez et al, 2012) and the second by siRNA gene silencing Morciano et al, 2009;Infantino et al, 2011a;Catalina-Rodriguez et al, 2012). Recently, by mutational analysis of the SLC25A1 gene (Edvardson et al, 2013;Nota et al, 2013), different mutations were identified in patients with agenesis of corpus callosum and hydroxyglutaric aciduria.…”
Section: The Multifunctional Role Of Citratementioning
confidence: 99%
“…This results in altered histone methylation marks and dysregulated cellular differentiation. Taking into consideration that the CIC gene has previously been implicated in epigenetic and cancer biology (Morciano et al, 2009;Wellen et al, 2009;Catalina-Rodriguez et al, 2012) and that CIC gene defect causes elevation of 2-HG (see section Citrate in Neurodevelopmental Syndromes and Hydroxyglutaric Aciduria), the previous hypothesis needs to be further focused and investigated. It is interesting to note that 2-HG can also increase in the absence of metabolic enzyme mutations.…”
Section: Citrate In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial extracts were generated as described (Morciano et al, 2009). The quality of the extracts was checked by western blotting using an antibody against the Sea/SLC25A1 mitochondrial marker (Morciano et al, 2009) diluted 1:2000.…”
Section: Mitochondrial Extract Analysismentioning
confidence: 99%